(untitled) (Business Vision, 2020)
The Mobile Unit of Integral Rehabilitation of Physiotherapy will be carried out in the municipality of Pasto-Nariño, which will provide home services, timely, effective and personalized health, physiotherapy and comprehensive rehabilitation, aimed at children, adolescents and adults, presenting various types of alterations: skeletal muscle, neurological and cardio-respiratory conditions where comfort, privacy and exclusivity will be offered throughout the rehabilitation process, generating for users their recognition of rights and inclusion in their daily lives, taking into account two primary factors: Functional rehabilitation and training of the user and their caregivers, for this purpose the mobile unit will have an interdisciplinary, competent and committed human team, as well as a specialized team of the latest technology for the adequate realization of the therapeutic plan that has been required, achieving well the improvement of the health and the quality of life of our users. The general objective is to carry out a feasibility study for the assembly of a mobile unit of Integral Rehabilitation of Physiotherapy in the municipality of Pasto-Nariño and to reach this objective five objectives have been raised that are related to the market study, the technical study, the administrative study, the financial study and the environmental study; the above in order to determine the viability of the same.